Preoperative Treatment of Locally Advanced Rectal Cancer - Schrag, Deborah; Shi, Qian; Weiser, Martin R.; Gollub, Marc J.; Saltz, Leonard B.; Musher, Benjamin L.; Goldberg, Joel; Al Baghdadi, Tareq; Goodman, Karyn A.; McWilliams, Robert R.; Farma, Jeffrey M.; George, Thomas J.; et al. (The New England journal of medicine, 2023)
In a trial comparing preoperative chemoradiotherapy and FOLFOX in patients with rectal cancer undergoing sphincter-sparing surgery, 5-year disease-free survival was 80.8% with FOLFOX and 78.6% with chemoradiotherapy.